A comprehensive overview of promising biomarkers in stage II colorectal cancer. (August 2020) - Parent, Pauline; Cohen, Romain; Rassy, Elie; Svrcek, Magali; Taieb, Julien; André, Thierry; Turpin, Anthony
Highlights: Adjuvant chemotherapy in stage II CC patients is guided by clinicopathologic findings. Novel biomarkers to lead to more accurate treatment decisions are an unmet clinical need. Clinical implications of prognostic biomarkers that need to be evaluated are reviewed. Immunoscore, ctDNA, and AI are the most promising markers, however these still require further validation. Abstract: Colon cancer (CC) has the highest incidence rate among gastrointestinal cancers and ranks the third in mortality among all cancers, which contributes to the current CC burden and constitutes a major public health issue. While therapeutic strategies for stage I, III, and IV CC are standardized, those for stage II CC remain debatable. The choice of adjuvant chemotherapy for patients with stage II CC depends on stage (pT4) and grade (high) of the disease, the presence of venous, perinervous, and/or lymphatic emboli, or the need of suboptimal surgery (tumor with initial occlusion or perforation needing emergency surgeries, <12 lymph nodes harvested). Several prognostic factors that have been validated in retrospective studies can potentially define a population of CC patients at low and high-risk for reccurence. The role of biomarkers is becoming increasingly important for the future personalized treatment options. We conducted a systematic overview of potential prognostic biomarkers with possible clinical implications in stage II CC.